Principal Strategies for Optimizing ARKAS and SIPLah to Improve BOSP Fund Accountability at SDN 6 Suak Tapeh - Edi Arwan; Dessy Wardiah; Wahid Ibrahim Banul Ngindom (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2026)
This study described and analyzed the principal's strategies, constraints, and solutions in optimizing the School Activity and Budget Plan Application (ARKAS) and the School Procurement Information System (SIPLah) to improve the accountability of School Operational Assistance (BOSP) funds at SDN 6 Suak Tapeh. A descriptive qualitative approach was employed. Informants were purposively selected and comprised a school supervisor, the principal, a classroom teacher, the school operator, and a school committee representative. Data were collected through interviews, observation, and document analysis. Trustworthiness was strengthened through source and method triangulation, and the data were analyzed using the Miles and Huberman model of data reduction, data display, and conclusion drawing. The findings showed that the principal optimized both applications through needs-based planning in ARKAS, teacher participation in identifying instructional priorities, clear role allocation, technical direction for the operator, continuous coordination with internal and external stakeholders, verification of ARKAS entries, need-oriented procurement through SIPLah, disciplined administration, physical and digital document archiving, and information disclosure to teachers and the school committee. Constraints included uneven technical understanding, dependence on the operator, unstable internet access, incomplete data and supporting documents, application updates, limited procurement options, competing school priorities, time constraints, and reporting demands. These constraints were addressed through coordination, technical assistance, task distribution, data verification, systematic archiving, consultation with relevant agencies, and continuous supervision. The study demonstrates that digital applications strengthen BOSP accountability only when supported by managerial, participatory, technical, and administrative leadership.